Biofungicidal Potential of Neosartorya (Aspergillus) Fischeri Antifungal Protein NFAP and Novel Synthetic γ-Core Peptides - Tóth, Liliána; Váradi, Györgyi; Boros, Éva; Borics, Attila; Ficze, Hargita; Nagy, István; Tóth, Gábor K.; Rákhely, Gábor; Marx, Florentine; Galgóczy, László (Frontiers in Microbiology, 2020)
Because of enormous crop losses worldwide due to pesticide-resistant plant pathogenic fungi, there is an increasing demand for the development of novel antifungal strategies in agriculture. Antifungal proteins and peptides are considered potential biofungicides; however, several factors limit their direct agricultural application, such as the high cost of production, narrow antifungal spectrum and detrimental effects to plant development and human/animal health. This study evaluated the safety of the application of antifungal protein and peptides from the ascomycete Neosartorya fischeri as crop preservatives. The full-length N. fischeri antifungal protein NFAP and novel rationally designed γ-core peptide derivatives (PDs), γNFAP-opt and γNFAP-optGZ exhibited efficacy by inhibiting the growth of the agriculturally relevant filamentous ascomycetes in vitro. A high positive net charge; however, neither the hydrophilicity nor the primary structure supported the antifungal efficacy of these PDs. Further testing demonstrated that the antifungal activity did not require a conformational change of the β-pleated NFAP or the canonically ordered conformation of the synthetic PDs. Neither haemolysis nor cytotoxicity was observed when the NFAP and γNFAP-opt were applied at antifungally effective concentrations in human cell lines. Similarly, the Medicago truncatula plants that served as toxicity model and were grown from seedlings that were treated with NFAP, γNFAP-opt or γNFAP-optGZ failed to exhibit morphological aberrations, reduction in primary root length or the number of lateral roots. Crop protection experiments demonstrated that NFAP and associated antifungal active γ-core PDs were able to protect tomato fruits against the postharvest fungal pathogen, Cladosporium herbarum.